The Effect of Profitability, Liquidity and Leverage on Tax Avoidance in Property Companies Listed on the Indonesia Stock Exchange (IDX) in the 2020-2023 Period - Murdiyanti MURDIYANTI; Nurul HIDAYAH (Journal of Governance, Taxation and Auditing, 2026)
This study aims to examine and analyze the influence of profitability, liquidity, and leverage on tax avoidance. This study observed 58 property companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. This study used a quantitative approach using cross-sectional data, which was then analyzed using multiple linear regression analysis using the SPSS application. Secondary data for this study came from the Financial Reports of Property Companies in Indonesia. The results showed that the independent variable, profitability, significantly influenced the dependent variable, tax avoidance. The effective tax rate or large tax burden of property companies can encourage them to engage in tax avoidance. Conversely, the independent variables, liquidity and leverage, did not significantly influence the dependent variable, corporate tax avoidance.